Conflict between criminal law, medical ethics and psychiatry demonstrated at the example of psychiatric court evaluation - Drakić Dragiša (Zbornik Radova: Pravni Fakultet u Novom Sadu, 2012)
The paper offers an analysis of the relationship between criminal law, on the one side, and medical science and psychiatry, on the other side, through an example of psychiatric court evaluation. Following introductory explanation, the author starts this analysis by examining the principle of freedom of an individual in criminal law and psychiatry. Later on, the author points to different perceptions of 'borderline psychic conditions' offered by the two scientific disciplines in the context of the quilt principle. After that he points to a number of other issues relating to psychiatric court evaluation which give rise to divergent positions of the criminal law and psychiatry in the criminal proceedings. Common to all such cases, in the opinion of the author, is the conduct of psychiatric court expert that is contrary to their professional code of ethics. In the end, the author concludes that the practice of the psychiatric court evaluation is detrimental to the interests of the criminal law and that it puts in grave jeopardy the ethics of psychiatry.